Entrepreneurship Education and Entrepreneur Development in Malaysian Higher Education: Policy, Challenges and Way Forward - Hamidon, Syahira (Universiti Teknologi MARA, 2012)
The purpose of this paper is to discuss and analyse efforts undertaken by the Government of Malaysia particularly through the Ministry of Higher Education (MOHE) to promote Entrepreneurship Education (EE) and entrepreneur development in Malaysian Institutions of Higher Learning (IHLs). The paper also discusses the opportunities and challenges facing the Ministry in promoting such efforts as well as suggestions on how to move forward.